PENGARUH BIMBINGAN GURU PENDIDIKAN AGAMA KRISTEN (PAK) TERHADAP MINAT BELAJAR SISWA. - Imelda Butarbutar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
The purpose of this study was to determine whether there is an effect of Guidance Christian religious education teacher on interest in learning of grade ten public senior high school Lumban Julu 2014/2015 ”. The research method used is quantitative research aims to study the effect of two variables, while the analysis used is to test the correlation hypothesis, namely the Product Moment and the tools used in data collection are to run a closed questionnaire. To determine whether there is the effect of Guidance Christian religious education teacher (X) on interest in learning (Y) of grade ten public senior high school Lumban Julu 2014/2015. the results result of this reseach shows that t = 5.593. To find out the correlation coefficient at a significant level of 5% where the t-table is 0.361, the t-test is used with the criteria t-count> t-table, so the hypothesis is accepted. The results of testing the hypothesis obtained that t = 5.593 turned out to be greater than t-table 0.361 (5.593> 0.361), thus the hypothesis is accepted. So it can be argued that,